2x-4(x+2)=(x+4)

Simple and best practice solution for 2x-4(x+2)=(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4(x+2)=(x+4) equation:



2x-4(x+2)=(x+4)
We move all terms to the left:
2x-4(x+2)-((x+4))=0
We multiply parentheses
2x-4x-((x+4))-8=0
We calculate terms in parentheses: -((x+4)), so:
(x+4)
We get rid of parentheses
x+4
Back to the equation:
-(x+4)
We add all the numbers together, and all the variables
-2x-(x+4)-8=0
We get rid of parentheses
-2x-x-4-8=0
We add all the numbers together, and all the variables
-3x-12=0
We move all terms containing x to the left, all other terms to the right
-3x=12
x=12/-3
x=-4

See similar equations:

| 54+7x=16x | | 1-5k=2k=16 | | 13x+4=13x-12 | | 36+x=54. | | 1/3x+5=1/3x+7 | | 1/3x+5=1/3x+-5 | | 2x-12-6x=28 | | 3j+16=-11 | | 3x5-x=56 | | 1/3x+5=1/3x+5 | | 30=2(2x+3) | | 2/3x+1/2=4/x+4/3 | | -1+2÷3+3t-1÷2=5t÷6+1 | | (100x^2+180x+81)^2=0 | | (b-5)/4=(b+8)/3 | | (x-3)(x+5)-(-2x-19)=0 | | 1/3x+15+15=x | | 2n=6n=0 | | Y=3/4x-10 | | X/8-3(x+5)=11 | | 5-4*x=-15 | | 4•(x+8)=3•(x-2) | | 3+x9=2 | | -3(5y+-7)=6 | | -64+16x²=0 | | 2x+6+38=5 | | -5n=3n=-10 | | -1,316+188m=0 | | 2x-12=8-4x | | 6x+4-2=10+ | | 0=-0.0444x^2+1.3333x | | 134=x+x+x-5+x-5 |

Equations solver categories